RESISTIRE D4.4: Summary report on qualitative indicators ... - Kent, Alexandra; Strid, Sofia; Sandström, Lina; Callerstig, Anne-Charlotte (Zenodo, 2023)
The aim of RESISTIRÉ is to understand the unequal impacts of the COVID-19 outbreak and its policy and societal responses on behavioural, social and economic inequalities and to work towards individual and societal resilience. RESISTIRÉ does so by collecting and analysing policy data, quantitative data and qualitative data in the EU27 (except Malta), Iceland, Serbia, Turkey and the UK, and translating these into insights to be used for designing, devising and piloting solutions for improved policies and social innovations, which in turn can be deployed by policymakers, stakeholders and actors in the field across different policy domains. This project process is repeated in three cycles, each step and cycle feeding the next one. Throughout the course of the three project cycles, research has consistently shown that already vulnerable and marginalised groups have become even more vulnerable and marginalised; existing inequalities have increased, and new ones have emerged (Axelsson et al. 2021; Cibin et al. ...